Review of Viruddha Ahara and its Effect on Healthy Life - Meena, Mamta Kumari; Sharma, Ashok Kumar; Sharma, K L; Meena, Rekh Raj; Nigam, Ayushi (International Research Journal of Ayurveda & Yoga, 2023)
Ayurveda is a vast and ancient medical science. Unlike other medical sciences, instead of focusing on treatment of any particular disease, Ayurveda focuses more on the healthy living and wellbeing of the patient. For healthy living, Ayurveda emphasizes on consuming right kind of diet which is healthy and nutritious. In Ayurvedic classics, Ahara (food) is mentioned as one among the three Upasthambas (Sub-pillars of body). Ahara is considered to be vital for a human body as it provides the basic nutrients, which are very essential to carry out the basic activities of digestion and metabolism. Ayurveda clearly defines that certain diet and its combinations, which interrupts the metabolism of tissue, which inhibits the process of formation of tissue and which have the opposite property to the tissue are called as Viruddha Ahara or incompatible diet. The concept of Viruddha Ahar is a unique to Ayurveda system. The food that has improper combinations or is wrongly processed is called Viruddha Ahar. Also, a time, season and quantity have their impact. Certain foods not consumed at a right time of a day (kaala), season (ritu) and proper quantities (matra) can also be classified as Viruddha ahar. The food which is incompatible in respect to climate, quantity, method of preparation, combination etc. are described as potent cause of both physical and psychological illnesses.